2023
DOI: 10.7554/elife.87993
|View full text |Cite
|
Sign up to set email alerts
|

SIRT-1 is required for release of enveloped enteroviruses

Abstract: Enterovirus D68 is a re-emerging enterovirus that causes acute respiratory illness in infants and has recently been linked to Acute Flaccid Myelitis. Here, we show that the histone deacetylase, SIRT-1, is essential for autophagy and EV-D68 infection. Knockdown of SIRT-1 blocks autophagy and reduces EV-D68 extracellular titers. The proviral activity of SIRT-1 does not require its deacetylase activity or functional autophagy. SIRT-1’s proviral activity is, we demonstrate, mediated through the repression of ER st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This finding is different from the CVB3 paper cited above, which shows TFEB translocation to the nucleus late during infection, indicating that CVB3 and EV-D68 may use TFEB somewhat differently. The disparity between EV-D68 and CVB3 regarding TFEB localization during infection is unsurprising since we have recently shown that the deacetylase SIRT-1, which deacetylates TFEB, is essential for EV-D68 release but not for CVB3 release (20). These findings suggest that EV-D68 and CVB3 can engage the same cellular process differently.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is different from the CVB3 paper cited above, which shows TFEB translocation to the nucleus late during infection, indicating that CVB3 and EV-D68 may use TFEB somewhat differently. The disparity between EV-D68 and CVB3 regarding TFEB localization during infection is unsurprising since we have recently shown that the deacetylase SIRT-1, which deacetylates TFEB, is essential for EV-D68 release but not for CVB3 release (20). These findings suggest that EV-D68 and CVB3 can engage the same cellular process differently.…”
Section: Discussionmentioning
confidence: 99%